2010
DOI: 10.1111/j.1464-0597.2009.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leadership and Employee Well‐Being: The Mediating Role of Trust in the Leader and Self‐Efficacy

Abstract: Although transformational leadership (TL) is considered a kind of positive leadership, which can elevate followers in the long term, the mechanism of how TL influences employee well-being remains a relatively untouched area. Based on survey data collected from 745 employees from the People's Republic of China (Beijing, n = 297; Hong Kong, n = 448), results revealed that employees' trust in the leader and self-efficacy partially mediated the influence of TL on job satisfaction, and fully mediated the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
260
3
16

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(292 citation statements)
references
References 63 publications
(104 reference statements)
13
260
3
16
Order By: Relevance
“…Cross-sectional research has found that employee self-efficacy and team efficacy both serve as links between transformational leadership and employees' psychological well-being ). In another study, an employee's self-efficacy and trust in the leader fully mediated the relation between transformational leadership and perceived work stress and stress symptoms, and partially mediated the link between transformational leadership and job satisfaction (Liu et al, 2010). Nevertheless, a relationship between transformational leadership and employee self-efficacy has not been found in all studies (e.g., Felfe and Schyns, 2002).…”
Section: The Role Of Personal Resources As Mediatorsmentioning
confidence: 95%
See 1 more Smart Citation
“…Cross-sectional research has found that employee self-efficacy and team efficacy both serve as links between transformational leadership and employees' psychological well-being ). In another study, an employee's self-efficacy and trust in the leader fully mediated the relation between transformational leadership and perceived work stress and stress symptoms, and partially mediated the link between transformational leadership and job satisfaction (Liu et al, 2010). Nevertheless, a relationship between transformational leadership and employee self-efficacy has not been found in all studies (e.g., Felfe and Schyns, 2002).…”
Section: The Role Of Personal Resources As Mediatorsmentioning
confidence: 95%
“…First, self-efficacy and meaningfulness of work are known to mediate the relationship between transformational leadership and employee well-being (e.g., Arnold et al, 2007;Liu et al, 2010;Nielsen et al, 2008) but have not earlier been studied as mediators in relation to depressive symptoms. Second, even though research has identified several mediators in the relationship between transformational leadership and employee well-being, we are so far unaware of the unique effects of these identified mediators.…”
Section: The Role Of Personal Resources As Mediatorsmentioning
confidence: 99%
“…Liu, Siu, & Shi, 2010). Usually, individuals’ well-being in work settings is closely related to organizational functioning.…”
Section: Introductionmentioning
confidence: 99%
“…When managers behave unpredictably, inconsistently or hypocritically, employees may show a greater inclination to leave (May et al, 2004). Liu, Siu and Shi (2010) found that continued positive relationships between manager and employee generated similar trustworthy and supportive relationships in social exchanges. These will positively affect relatedness satisfaction.…”
Section: Manager Relations and Satisfying Psychological Needsmentioning
confidence: 99%